A new remarkably preserved fossil assassin bug (Insecta, Heteroptera, Reduviidae) from the Eocene Green River Formation of Colorado. (19th January 2021) - Swanson, Daniel R.; Heads, Sam W.; Taylor, Steven J.; Wang, Yinan
Abstract: We describe a new Eocene fossil assassin bug, Aphelicophontes danjuddi gen. et sp. nov. (Reduviidae: Harpactorinae), from the Green River Formation of Colorado. The specimens informing this description are extraordinarily preserved, particularly in the external and internal structures of the adult male genitalia. We discuss implications of the new species for the systematics and evolutionary history of the group, as well as the strength of phylogenetic signal in harpactorine genitalia.